Multipe Regression and Productivity Analysis of Modjopanggung Sugar Factory - mutaqin, tatag; Yudoko, Gatot (Journal of Business and Management, 2012)
Modjopanggung sugar factory is located in Tulungagung have problem in sugar production and productivity that less effective, based on that case, question of this research is  about some factor of productivity, how to increase sugar production, and productivity, and the purpose is to know the most significance factor that influence sugar production and to measure productivity of Modjopanggung in 2010.The step to start this research, first problem formulation, theoretical foundation, model formulation, data collection and analysis, and conclusions and recommendations. In this research use multiple regression model that use sugar production as dependent variable ,and factories sugarcane own field wide, farmer sugarcane field wide, sugarcane sucrose content  average from factories sugarcane field,sugarcane sucrose content average from farmer sugarcane field, factories efficiency, truck unit, yesterday sugarcane remnant ,sugar milling day amount, milling capacity as independent variable, and in productivity measure use labor, sugarcane material, capital, fuel, electricity as input and income from sugar and tetes as output. Methodology of research is by interview and observation to factory. The result is amount of truck unit and farmer sucrose content is the most significant among all variable to increase sugar production with positive sign, mean increase in them also increase sugar production, adjusted r square 0.997 mean 99.7% of sugar production can explained by result of independent variable, t value in 0.1298 that still inside acceptance area, mean no difference in forecast and reality of sugar production. Productivity in 2010, ratio of partial output and input all more than 1 mean output can cover input, but in multifactor and total factor less than 1  mean addition of input productivity factors actually can not cover by output factor, with lowest partial output factor is electricity and highest partial output factor is sugarcane material. The suggestion is better policy to increase truck unit and farmer’s sugarcane content and effectivity in labor quality, sugarcane dividend with farmer, capital usage, fuel alternate and usage, electricity efficiency. Keywords: Sugarcane production, multiple regressions, productivity analysis, PG Mojopangung